1991
DOI: 10.1159/000174889
|View full text |Cite
|
Sign up to set email alerts
|

Seminars in Thrombosis, Thrombolysis, and Vascular Biology

Abstract: The fundamental determinants of coronary blood flow include the vessel radius, pressure gradient, and the physical characteristics of the cellular components and fluid medium. Specifically, cellular rheology and plasma viscosity determine, to a significant degree, both macro- and microcirculatory blood flow, particularly when either is compromised by existing atherosclerotic narrowing or reperfusion injury. Among individuals with coronary heart disease, abnormalities in cellular rheology and plasma viscosity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…There is a small literature strongly suggesting that several factors related to blood viscosity are adversely affected by hypohydration (16)(17)(18)(19)(20)(21)(35)(36)(37)(38)(39) and that these rheologic factors predict the risk of coronary heart disease (4,6,8,9). Whole blood viscosity is determined mainly by hematocrit and fibrinogen levels, both of which have frequently been associated with coronary heart disease events (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a small literature strongly suggesting that several factors related to blood viscosity are adversely affected by hypohydration (16)(17)(18)(19)(20)(21)(35)(36)(37)(38)(39) and that these rheologic factors predict the risk of coronary heart disease (4,6,8,9). Whole blood viscosity is determined mainly by hematocrit and fibrinogen levels, both of which have frequently been associated with coronary heart disease events (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…In some reports, the magnitudes of their effects are comparable with those of smoking, diastolic blood pressure, and low density serum cholesterol (2,4,6). These hemorheologic factors are found to be elevated years before manifestation of acute ischemic events (4) and are implicated in the early stages (6), acceleration (8), and extent (9) of atherosclerosis, as well as prognosis in patients with arteriosclerotic disease (5,10). They are also associated with hypertension (11) and intermittent claudication (12).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…A large number of studies have demonstrated that vascular cells play a critical role in maintaining the normal functions of blood vessels. 28,29 According to the basic principle of tissue engineering, vascular cells are the initial candidates for vascular regeneration.…”
Section: Terminally Differentiated Vascular Cellsmentioning
confidence: 99%